Factors contributing to job performance at Malaysian Maritime Enforcement Agency (MMEA) / Sahaziera Sahak - Sahak, Sahaziera (2014)
This research is conduct to carry out “Factors contributing to job performance at Malaysian Maritime Enforcement Agency (MMEA)”. The objectives are to identify the levels of job performance at MMEA and the dominant factors that influence job performance as well as to determine the relationship between those factors with job performance. In this study, it consists of four factors that contribute to job performance the researcher interest to study on. Convenience sampling techniques was used to get the data that are required. Population of the research was the head quarter of MMEA located at Putrajaya. 100 respondents involved for accomplished the research by answering the questionnaires. All the data collected through the question were analysed systematically by Statistical Package for Social Science (SPSS). The conclusion of this study was the outcome from the data analysis and findings. A clear findings and results were observed based on frequency and descriptive statistic. Besides, to answer the research objectives Pearson’s Correlation and Multiple Regression have been done. The finding showed that the dominant factor that influences job performance at MMEA is personality. The recommendation is also provided in this research to emphasize the important of job performances in MMEA.